Penerapan Teknik Analytical Hierarchi Process (AHP) Dalam Pengambilan Keputusan Pembiayaan Produktif (Studi Kasus Pada Bank JATIM Syariah Cabang Darmo) - Firdausi Nuzula; Dina Fitrisia Septiarini (Universitas Airlangga, 2016)
The purpose of this study was to determine the main criteria of decision-making for productive financing based on the level of interest by using AHP technique. Results of this study is the capital criteria become a major criterion in the decision-making productive financing. Most important sub-criteria of Character is payment commitments. Most important sub-criteria of Capacity is obtained from customer turnover per month. Most important subcriteria of Capital is trackrecord of prospective customer payments. Most important subcriteria of Collateral is the ownership of the collateral and the authenticity of the documents. Most important sub-criteria of Condition of Economy is the business both in the side of the law and the government. The results of all the weighting of criteria and sub-criteria through the process of harmonic average from seventh informant’s answers.